Melanotic Neuroectodermal Tumor of Infancy in the Maxilla - Daniel Falbo Martins de Souza; Daniel Isaac Sendyk; Juliana Seo; Eduardo Vasques da Fonseca; Maria da Graça Naclério-Homem; Maria Cristina Zindel Deboni (Hindawi Limited, 2013)
Melanotic neuroectodermal tumors of infancy (MNTIs) are rare fast-growing tumors with high recurrence rates. These tumors, which originate in the neural crest, commonly occur in the anterior maxilla of children under the age of one. Here, we describe an MNTI case in a two-month-old girl with increasing swelling in the left cheek. MNTI was diagnosed in this case following tomography and biopsy. The patient's histological and immunohistochemical profile indicated a remarkable combination of neural, melanocytic, and epithelial cell differentiation. One year following tumor excision, a follow-up examination revealed that the child exhibited no tumor recurrence. Approximately 260 cases of MNTI have been reported since this type of tumor was first described. In the present case, early diagnosis minimized the difficulties and risks associated with treatment and facilitated an optimal outcome. Despite complete surgical excision, careful followup is recommended. In addition, maxillary functional orthopedics and reconstruction may be necessary in cases of MNTI.